Additive Manufacturing of Poly(propylene) by Means of Melt Extrusion - Hertle, Sebastian; Drexler, Maximilian; Drummer, Dietmar (Macromolecular Materials and Engineering, 2016)
Keywords: additive manufacturing; fusion bonding; melt extrusion; poly(propylene) (PP); thermoplastics

Air inclusions in the polymer melt functioning as intrinsic physical blowing agents for the generation of foams in rotational molding - Werner, Jannik; Vetter, Lukas; Hertle, Sebastian; Wolf, Michael; Drummer, Dietmar (Cellular Polymers, 2020)

Analyse der Temperaturführung in der roboterbasierten Materialextrusion mit Polypropylen - Hertle, Sebastian; Wörz, Andreas; Drummer, Dietmar (Proceedings of the 16th Rapid.Tech Conference, 2019)

Berücksichtigung des Druckniveaus bei der Viskositätsermittlung im Hochdruckkapillarrheometer - Hertle, Sebastian; Mattner, Tobias; Drummer, Dietmar (9. CONNECT! European Moldflow User Meeting 2018, 2018)

Development Of An Integrated Simulation Method For The Prediction Of Transmission Errors Of Injection Molded Spur Gears - Schubert, Dominik; Hertle, Sebastian; Kleffel, Tobias; Drummer, Dietmar (22nd International Conference on Material Forming (ESAFORM 2019), 2019)

Development of a simulation method for the prediction of transmission errors of injection molded spur gears - Schubert, Dominik; Hertle, Sebastian; Kleffel, Tobias; Drummer, Dietmar (AIP Conference Proceedings, 2019)
Due to the cost-efficient injection molding process and its high degree of freedom in design injection molded gears are widely used in actuating drives. One important functional requirement is the positioning precision of these systems. In gear applications, this precision is mostly dependent on the transmission error. Therefore, a lot of effort in mold design and construction is spent on ensuring acceptable transmission errors of injection molded plastic spur gears. To predict the transmission error of injection molded spur gears, an integrative simulation method is developed in this work. First, the injection molding process is simulated. The resulting gear geometry is transferred to the mechanical model of a flank-rolling test to evaluate the transmission error. The transmission error is mainly dependent on the local shrinkage and warpage caused in the solidification processes during injection molding, which in turn are influenced primary by tool design and process parameters. It is shown, that accurate simulation results concerning gear geometry, require a precise modeling of the process, tool and material. This includes accurate modelling of injection and temperature parameters, gate and cooling design, and behavior of the material. The simulation of the flank-rolling test has to take the specified reference torque and testing speed into account to ensure a realistic prediction of the resulting transmission errors. The research is done on gears with module 1 mm and 39 teeth. According to the model, the gate design has the highest influence on the transmission error. An increase in transmission error of 100% is predicted for gears with three symmetric pin-point gates compared to a central pin-point gate, and an increase of 50% for an eccentric pin-point gate. Therefore, if sufficiently modeled, a realistic prediction of transmission errors is possible.
CRIS-Team Scopus Importer:2019-07-23

Einfluss der druckabhängigen Viskosität auf die Spritzgusssimulation kurzfaserverstärkter Thermoplaste - Hertle, Sebastian; Drummer, Dietmar (Technomer 2017, 2017)

Einfluss prozessbedingter Gefügestrukturen auf die Zahnfußtragfähigkeit von POM-Stirnrädern - Schubert, Dominik; Hertle, Sebastian; Drummer, Dietmar (Konstruktion, 2019)

Einfluss prozessbedingter Gefügestrukturen auf die Zahnfußtragfähigkeit von POM-Stirnrädern - Schubert, Dominik; Hertle, Sebastian; Drummer, Dietmar (Konstruktion, 2019)
In research on polymer gears, materials are often specially modified to expand thermal, mechanical, and tribological application limits, without considering processing conditions. However, there is a big influence of processing conditions on the resulting microstructure of polymer gears, which determines application limits. This paper shows, how a processing strategy for an optimised microstructure can lead to significant increases in durability of polymer gears.
CRIS-Team Scopus Importer:2021-04-20

Influence of the thermomechanical properties on the joining of adhesion incompatible polymers by form-fit using the vibration welding process - Wolf, Michael; Hertle, Sebastian; Drummer, Dietmar (eXPRESS Polymer Letters, 2019)

Influence of titanium oxide-based colourants on the morphological and tribomechanical properties of injection-moulded polyoxymethylene spur gears - Schubert, Dominik; Hertle, Sebastian; Drummer, Dietmar (Journal of Polymer Engineering, 2019)
Regardless of colouration for functional or aesthetic purposes, technical polymer parts, like gears, require consistent properties. However, there is a lack of research into the effect of colourants on the tribomechanical properties of gears. Therefore, the effects of two pigments, titanium dioxide (white) and chrome antimony titanium oxide (yellow), and three delivery methods, masterbatch, liquid colour and direct compounding, on part morphology, dimensions, tribological and mechanical performance of injection-moulded polyoxymethylene (POM) spur gears are investigated in this paper. The white pigment accelerates the crystallisation of POM, causing fine and highly-crystalline morphological structures and smaller dimensions. However, the yellow pigment decelerates crystallisation, resulting in a coarser morphology with highly crystalline core material and bigger parts. Furthermore, the delivery method affects only the tribomechanical properties. Using a masterbatch decreases loads at break and increases deflection at break, since the carrier material acts as an impact modifier and a weak spot. The liquid colour decreases wear due to lubricating properties, whereas the pure pigments increases abrasion, especially in combination with a coarse microstructure. However, the effects of carrier systems and changes in morphology are always superimposed. Considering the performance and tolerance of technical components, colourants have to be carefully selected to ensure beneficial properties.
CRIS-Team Scopus Importer:2019-08-16
Keywords: colouration; nucleation; polymer gears; tribology; wear

Influence of Vacuum on the Porosity and Mechanical Properties in Rotational Molding - Vetter, Lukas; Werner, Jannik; Wolf, Michael; Hertle, Sebastian; Drummer, Dietmar (Polymer Engineering and Science, 2019)
Rotational molding allows the production of seamless, hollow parts with a high degree of design flexibility. Nevertheless, the process has limitations such as long cycle times as long holding times are necessary to produce components free of air inclusions. Within the scope of this article, an experimental setup was developed to evaluate the possibility and resulting effects of using vacuum in the rotational molding process. For this purpose, trials with different vacuum pressure levels and holding times were carried out and the resulting porosity and surface quality as well as the mechanical properties of the specimens were determined. The investigations showed that the use of vacuum allows a significant reduction in porosity even at low holding times, which can considerably reduce the cycle time of the process. However, the extent of possible time saving is limited by the requirement of a good surface quality, on which the vacuum application shows no effect. Furthermore, the mechanical properties of the parts could be slightly improved by using vacuum. POLYM. ENG. SCI., 2019. © 2019 Society of Plastics Engineers.
CRIS-Team Scopus Importer:2019-06-25

Integrative simulation method for the prediction of anisotropic and time-dependent mechanical behavior of injection molded fiber-reinforced fan impellers - creep modelling - Hertle, Sebastian; Lass, Andre; Wurm, Frank-Hendrik; Drummer, Dietmar (fan 2018, 2018)

Integrative simulation method for the prediction of anisotropic and time-dependent mechanical behavior of injection molded fiber-reinforced fan impellers - numerical and experimental approach - Lass, Andre; Hertle, Sebastian; Drummer, Dietmar; Wurm, Frank-Hendrik (fan 2018, 2018)

Layer-dependent characterization of wear behaviour on variothermal injection moulded micro parts using pin on disc measurements - Meister, Steve; Hertle, Sebastian; Drummer, Dietmar (Microsystem Technologies-Micro-And Nanosystems-Information Storage and Processing Systems, 2017)

Mechanisches Verhalten lasergesinterter PA12 Bauteile bei variierenden statischen Belastungsgeschwindigkeiten und -dauern - Wörz, Andreas; Hertle, Sebastian; Drummer, Dietmar (Proceedings of the 16th Rapid.Tech Conference, 2019)

Micrometer accurate measurement of tooth wear - Gierl, Bernhard; Hertle, Sebastian; Kleffel, Tobias; Drummer, Dietmar (Kunststoffe International, 2019)
CRIS-Team Scopus Importer:2019-10-08

New Approach on the Allocation of Wear Allowances - a Case Study - Schubert, Dominik; Rohrmoser, Andreas; Hertle, Sebastian; Wartzack, Sandro; Hagenah, Hinnerk; Merklein, Marion; Drummer, Dietmar (22nd International Conference on Engineering Design (ICED19), 2019)

Production of polymer-metal hybrids using extrusion-based additive manufacturing and electrochemically treated aluminum - Hertle, Sebastian; Kleffel, Tobias; Wörz, Andreas; Drummer, Dietmar (Additive Manufacturing, 2020)
The development towards higher individualization and functional density pushes the need towards a flexible production of multi-material and lightweight components. In this paper, extrusion based additive manufacturing was used to produce polymer-metal hybrids with polypropylene and aluminum alloy. For this purpose, a screw-driven extruder on a six-axis robot was used. Due to the adhesion incompatibility of polypropylene and untreated metals, the surface of the aluminum sheets was electrochemically micro-structured. The investigations show that this enables a mechanically stressable joint through the filling of the surface microstructures with polymer. Investigations on lap shear joints reveal a distinct influence of the contact temperature between the polymer and metal onto the lap shear strength. A sufficient contact temperature is required for filling surface microstructures. Thus, increased metal and extrusion temperatures favor higher strengths. Furthermore, the use of a consolidation roll shows beneficial influences in lower temperature ranges due to the application of higher pressures during the polymer strand deposition.
CRIS-Team Scopus Importer:2020-02-28
Keywords: Consolidation; Lap shear strength; Material extrusion; Polymer-metal-hybrid; Surface microstructure